Targeted 16S rRNA high‐throughput sequencing to characterize microbial communities during composting of livestock mortalities - Tkachuk, V.L; Krause, D.O; Knox, N.C; Hamm, A.C; Zvomuya, F; Ominski, K.H; McAllister, T.A (Journal of applied microbiology, 2014)
AIM: A comprehensive understanding of the microbial community is necessary to ensure a significant reduction in pathogens during the composting process. METHODS AND RESULTS: Two biosecure, static composting systems containing cattle mortalities were constructed at subzero temperatures. Temperature at each sampling site was measured continuously and samples were grouped as either ≤50 or ≥55°C, based on temperature exposure required for effective pathogen inactivation during composting. High‐throughput 454 sequencing was used to characterize the bacterial communities within each sample. Clustering of bacterial communities was observed according to temperature. However, neither richness nor diversity differed between temperature groups. Firmicutes was the most abundant phylum within both temperature groups but was more pronounced (63·6%) in samples ≥55°C (P < 0·05). Similarly, members of Clostridia, Clostridium sensu stricto (3·64%), Clostridium XI (0·59%), UF (Clostridiaceae 1) (5·29%) and UF (Clostridiales Incertae Sedis XI) (6·20%), were prominent at ≥55°C (P < 0·05), likely a reflection of spore survival and/or anaerobic microenvironments within passively aerated compost piles. Members of Thermobifida (3·54%), UO (Actinomycetales) (12·29%) and UO (Bacillales) (19·49%) were also prominent at ≥55°C (P < 0·05). CONCLUSION: Substantial spatial diversity exists within bacterial communities in field‐scale compost piles. Localized temperature at the site of sampling may be one of the factors contributing to this phenomenon. SIGNIFICANCE AND IMPACT OF THE STUDY: This is the first study to describe the microbial community profile with the use of targeted 16S rRNA high‐throughput sequencing in passively aerated composted livestock mortalities.